Hubungan Antara Sumber Informasi, Uang Saku Dengan Perilaku Gaya Hidup Sehat Mahasiswi Tingkat Tiga Prodi DIII Kebidanan Universitas MH Thamrin Jakarta Timur - Ella Nurlelawati; Kursih Sulastriningsih; Riza Umami (Akademi Keperawatan RSPAD Gatot Soebroto, 2019)
Globalization and technological development in each field also influence changes in behavior, people’s lifestyles, such as dietary habits, physical activity, smoking behavior, length of sleep, stress control clean and healthy living behavior. The study’s aims to determine the relationship between information sources, and pocket money with healthy lifestyle behaviors for third-level female students at the Diploma III of Midwifery study program at MH Thamrin University, East Jakarta 2016. Methods that is used is a cross- sectional design carried out for two months produced by Midwifery MH Thamrin University, East Jakarta. Information Source test results are information with healthy lifestyle behaviors indicate that information sourced from the media has healthier healthy lifestyle behaviors (79.7%). In proportion, pocket money with healthy lifestyle behavior shows that an allowance of more than one million five hundred thousand rupiahs has a healthy lifestyle behavior of 88.9% (56 respondents) compared to an allowance of less than one million five hundred thousand rupiahs of 66, 7% (20 respondents), p = 0.02, OR = 4.00 which means that respondents with an allowance of more than one million five hundred thousand rupiahs have a 4 times chance of having a healthy lifestyle compared to respondents with an allowance of less than one million five hundred thousand rupiah. Conclusion of the research are respondent with sources of information through the media have a one-time opportunity to have a healthy lifestyle an respondents with a monthly allowance of more than one million five hundred thousand rupiahs have a 4 times opportunity to have a healthy lifestyle Keywords: Healthy Lifestyle Behavior, Information Sources, Pocket Money